Desain Karakter Untuk Pencak Silat PSHT Kota Surabaya - Muchammad Iqbal; Aris Sutejo; Sri Wulandari (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
Pencak silat is not only interpreted as a martial art, but also as a medium for character building and life values. The Persaudaraan Setia Hati Terate (PSHT) has teachings about brotherhood, courage, and social responsibility that need to be communicated in a relevant way in today's visual era. This design aims to create a character that represents the identity of PSHT Surabaya through a Research and Development (R&D) method with the stages of Planning, Production, and Evaluation (PPE). As a result, the rooster character was chosen as a symbol because it reflects the philosophy of courage and exemplary behavior. This design is expected to become a communicative visual identity while strengthening the organization's image.